If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5q + 8 = -6q + -12 Reorder the terms: 8 + -5q = -6q + -12 Reorder the terms: 8 + -5q = -12 + -6q Solving 8 + -5q = -12 + -6q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '6q' to each side of the equation. 8 + -5q + 6q = -12 + -6q + 6q Combine like terms: -5q + 6q = 1q 8 + 1q = -12 + -6q + 6q Combine like terms: -6q + 6q = 0 8 + 1q = -12 + 0 8 + 1q = -12 Add '-8' to each side of the equation. 8 + -8 + 1q = -12 + -8 Combine like terms: 8 + -8 = 0 0 + 1q = -12 + -8 1q = -12 + -8 Combine like terms: -12 + -8 = -20 1q = -20 Divide each side by '1'. q = -20 Simplifying q = -20
| 1x+27x+8x=818004 | | (2x+1)(7x+5)=0 | | 4x^2-9+25y^2-20xy= | | 54=2w+2l | | 2a+b+c=24 | | 2x+12=6x-52 | | 2(n+5)=n+15 | | -3t^2+24t-36=0 | | -wv+6w+wv-5w= | | 2(-1)+1-(-1-2)=2-(-2)(-1) | | x*3+3x=19 | | (5+2x)6-4x=11-7x | | 8q^2-5q=7q^2-9q+12 | | x(x+4)=117 | | 24=12-4x | | y=20-2p | | 2(-1)-(-1-2)=2-(-2)(-1) | | 4(t-9)=(t+7) | | 4(n-2)=2n+30 | | 3(5-2n)=35 | | 37-17=4(x-7) | | x-20=20.3 | | b+6=10 | | 45*30=9x | | 2.8ab+b^2=0 | | 3(n+4)=n+20 | | 21-11=2(x-6) | | 500-2x=318 | | 2x-8x+1=910x | | -5(w-9)+8w+1= | | -5=35 | | 15x+60=16x |